Iklan Layanan Masyarakat Dalam Mengurangi Kecelakaan Lalu Lintas di Polres Pematangsiantar - Rury Cassa Pirera (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2019)
A problem of traffic accident and to an accident into a a result of the current social problem .Human sacrifices in this case it could be in a state of died , suffered severe injuries , minor injuries and can cause material loss and damage to the vehicles involved in .Public relations pematangsiantar through police accident unit in reducing an accident for riders with put advertising banners appeals addressed to the message of the banners that affected attitude the rider when read it .Research methods that were used method of qualitative descriptive .This research result indicates that persuasive communication public relations pematangsiantar police largely through advertising banners in reducing an accident for the rider been going very well . n the use of banners required characteristic of banners as installment area banners , design banners , clarity editor and size of banner for attracted the interest of the rider within view and read banners persuasive so the message delivered with good to motorists who saw it.